2-(2-Azabicyclo[3.2.1]octa-3,6-dien-2-yl)-1,3-dimethoxyimidazolium hexafluoridophosphate - Simone Haslinger; Gerhard Laus; Klaus Wurst; Herwig Schottenberger (IUCrData, 2016)
The title salt, C12H16N3O2+·PF6−, was obtained by the dipolar cycloaddition of norbornadiene to 2-azido-1,3-dimethoxyimidazolium hexafluoridophosphate. The methoxy groups attached to the imidazolium ring of the cation adopt an anti conformation [displacements of the C atoms from the ring plane = 1.386 (4) and −1.404 (3) Å]. In the crystal, weak inter-ionic C—H...F contacts are observed. The structure was refined as a two-component twin. Positional disorder of the fluorine atoms of the PF6 anion was observed, the occupancy ratio being 0.562 (16):0.438 (16).